Canadian Annual Review of Politics and Public Affairs 1970 - Forster, Donald F.; Saywell, John T., 1929-2011 (Book collections on Project MUSE., 1971)
Canadian Annual Review is the work most frequently consulted by librarians, public speakers, businessmen, economists, political experts, news analysts, historians, and political scientists. To anyone who is required to deliver an address, to write a paper, to make a submission, or to erview the development of one of the phases of Canadian life with which it deals, this volume will prove of inestimable value. The Review contains reports by well-known contributors on events of the year in Parliament and politics (with essays on each of the provinces), external affairs and defense, the national economy, and Canadian life and leisure activities.